Sivilasjonens sårbarhet David Humes analyse av samfunnsmessig utvikling - Petter Nafstad (Scandinavian University Press (Universitetsforlaget), 2017)
The book describes and interprets the Scottish philosopher and historian David Hume's theory of the basis of a society's development from barbarism to civilization and for the maintenance of a civilized society. An analysis of the development and maintenance of civilization should, according to Hume, be conducted along three dimensions, a political, an economic and one concerning civil society. Therefore, the three main parts of the book analyses Hume's treatment of these three social spheres. Hume's example of a successful development from barbarism to civilization is England, but he also means that an analysis of English past and present will yield a more general understanding of civilizing processes. However, even civilized societies contain disintegrating forces and therefore potentials for regression to non-civilized conditions. An example would be radicalized political and religious ideologies. The sources are mainly Hume's The History of England and his many essays on contemporary English conditions